ENSINO FUNDAMENTAL DE 9 (NOVE) ANOS:a universalização do acesso, a permanência qualitativa na escola e as contradições do processo de implantação em São Luís - Leal, Maria do Perpetuo Socorro Lima (2011)
This paper, entitled ELEMENTARY SCHOOL WITH 9 YEARS: universal access, qualitative permanence in school and the contradictions in the implementation process in Sao Luis , is part of the Master s Degree in Education, Basic Education Policy research group of the Federal University of Maranhao. Considering the Brazilian educational context, the research focus on the Policy for the Expansion of the Elementary School to 9 years, which included the six-year-old children into the compulsory schooling. The main goal of this paper is to investigate the policy implementation process in the City Department of Education (SEMED), taking as reference the approach to public education policies in the context of State reform. The specific goals consist in identifying the main demands and challenges faced by the City schools, as well as to analyze the conceptions the professionals have regarding such policy. The normative compendium, especially the Federal Constitution, the National Education Basis and Guideline Law and the 11.274/2006 Law, which expands to 9 years the elementary school previously with 8 years, as well as the subject bibliography, especially the following authors: Cury (1995); Abádia (2002) and Shiroma (2000) have helped in this research. The questionnaire for the data collection was organized considering two central categories: the design of the Policy for the Expansion of the Elementary School to 9 years and the design of its implementation process in SEMED. The research subjects were SEMED s professionals and former professionals: coordinators, teachers, teachers trainers, superintendents, principals and directors. The analyses show that the Policy for the Expansion of the Elementary School to 9 years in SEMED is part of a major project of national education public policy promotion, thus, as a local unfolding of the national policy, it did not effectively consider the democratic principles for the qualitative permanence of the students in the childhood cycle in the elementary school with 9 years. Review of curriculum, continuing education policy reformulation, ensuring schools physical and structural conditions are some of the challenges to be faced by SEMED in the recognition process of the right to education. The research also shows SEMED s professionals high levels of commitment in the seeking to achieve an educational project able to pay the social debt with the six-yearold students, as well as with all elementary school students.